Rediscovery, amplified description, and taxonomic re-evaluation of Phanera erythropoda var. guangxiensis (Leguminosae, Cercidoideae) - Peng, Xia; Jiang, Kai-Wen; Xie, Zhi; Gu, Shi-Ran; Wang, Xiang-Ping; Li, Shi-Jin; Shi, Miao-Miao; Tu, Tie-Yao; Zhang, Dian-Xiang (Phytotaxa, 2024)
For nearly seven decades, the legume variety Phanera erythropoda var. guangxiensis (D. X. Zhang & T. C. Chen) Mackinder & R. Clark has been known solely from its type gathering, which lacked flowers and possessed only immature fruits. We report the rediscovery of this elusive variety at its type locality in Guangxi, China, including specimens bearing mature flowers. The floral characters observed diverge significantly from those of P. erythropoda, yet exhibit clear affinities with the Lasiobema group within the genus Phanera. With these new data, we provide a comprehensive description of the variety and propose elevating its taxonomic status to that of a distinct species, namely Phanera guangxiensis. We also present an updated key to all Chinese members of the Lasiobema group.